Towards high-energy, high-resolution computed tomography via a laser driven micro-spot gamma-ray source. Issue 1 (December 2018) - Wu, Y.; Zhu, B.; Li, G.; Zhang, X.; Yu, M.; Dong, K.; Zhang, T.; Yang, Y.; Bi, B.; Yang, J.; Yan, Y.; Tan, F.; et al.
Abstract Computed Tomography (CT) is a powerful method for non-destructive testing (NDT) and metrology awakes with expanding application fields. To improve the spatial resolution of high energy CT, a micro-spot gamma-ray source based on bremsstrahlung from a laser wakefield accelerator was developed. A high energy CT using the source was performed, which shows that the resolution of reconstruction can reach 100 μm at 10% contrast. Our proof-of-principle demonstration indicates that laser driven micro-spot gamma-ray sources provide a prospective way to increase the spatial resolution and toward to high energy micro CT. Due to the advantage in spatial resolution, laser based high energy CT represents a large potential for many NDT applications.